Strukturális folyamatok a vágósertés-piacon az EU-csatlakozás után - Csonka, Arnold (Közép-Európai Közlemények, 2012)
Since the Change of Regime in Hungary (1989), and especially after the country’s accession to the European Union (2004), the domestic pork product chain has faced its greatest challenge in which producing and processing industries were mainly affected. Despite the fact that the accession took place six years ago, domestic participants situated in the lower levels of product chain are still greatly threatened by trade and competition within the EU. This permanent threat can not be cured by intervention either by state or red tape. The operators of slaughter pig market have to volunteer to work out common strategic movements and tactical steps to find a solution. In order to find successful strategies, the characteristics of transactions about quality, quantity, price and others have to be known. In my dissertation I have dealt with the tangible and measurable aspects of such processes. By means of structural comparison of domestic and foreign pig farming, it may be concluded, that the extremely scattered system of home pig breeding means a severe competitive disadvantage in the EU. In order to decrease our competitive disadvantage – besides real concentration and centralization of capital – more roles have to be given to organizations based on joint estates and integrations coordinated by market contracts.